Lattice Numerical Simulations of Lab-Scale Hydraulic Fracture and Natural Interface Interaction - Bakhshi, E.; Rasouli, V.; Ghorbani, A.; Fatehi Marji, M.; Damjanac, B.; Wan, X. (Rock mechanics and rock engineering, 2019)
Hydraulic fracturing is the prime technology for enhancing production from unconventional reservoirs. Design and operation of hydraulic fracturing requires adequate knowledge of formation properties, in situ stresses and fluid properties, due to its complex nature. One of the challenges, that have been the subject of many past studies, is the interaction mechanism when hydraulic fracture intersects a natural interface (e.g., natural fracture or interbed). Crossing, arresting and opening are the known interaction mechanisms. The formation properties, state of in situ stresses, stress contrast, strength properties of the interface, angle of intersection and injecting fluid characteristics affect the interaction mechanism to different extents. The use of numerical models is widespread in simulation of hydraulic fracturing. The use of methods based on the continuum (e.g., FEM) and discontinum (e.g., DEM) representation of media is subjected to some limitations in predicting the correct geometry of the propagating fracture. Lattice method, which is based on the bonded particle approach, has shown promise in simulating hydraulic fracturing. In this paper, lattice modeling is used to simulate the interaction mechanism of lab experiments carried out on mortar samples but at larger scales. The cubical mortar samples of 10 cm size had two synthetically built natural fractures with different angles of approach and filled with different types of glue. The effect of intersection angle and the mechanical properties of the interface were simulated numerically under conditions of viscosity-dominated fracture propagation regime as occurred in the lab. The results demonstrate the advantages of lattice simulation to study the impact of each parameter on the fracture interaction. A larger angle of approach and stronger glues are shown to promote the crossing mode. The shear strength and stress anisotropy are the main parameters influencing the interaction mechanism.